|Therapeutic and preventive effects of apigenin in cerebral ischemia: a review. Issue 22 (31st October 2022) - Wang, Xu; Li, Jinjian; Zhao, Dexi; Li, Jinhua
Abstract : APG can exert various protective effects against cerebral ischemia. Moreover, APG has shown a highly promising ability to prevent cerebral ischemia in terms of regulating blood glucose, blood pressure, lipids and gut microbes. Abstract : Cerebral ischemia is one of the major global health problems, but the treatment for it is currently very limited. A tissue plasminogen activator, the only drug effective in the treatment of cerebral ischemia, has a narrow time window and strict contraindications, resulting in only a small percentage of patients benefiting from it. Apigenin (APG) is a natural phytoestrogen flavonoid, widely found in vegetables and fruits including parsley, Chinese celery and chamomile. APG has shown good neuroprotective effects in animal models of many neurological diseases. For the first time, we report a review of the neuroprotective effects of APG in cerebral ischemia. We came to the conclusion that APG can exert various protective effects against cerebral ischemia, including anti-oxidative stress, anti-inflammatory, anti-autophagic, anti-apoptotic and other neuroprotective effects. Moreover, APG has shown a highly promising ability to prevent cerebral ischemia in terms of regulating blood glucose, blood pressure, lipids and gut microbes. The aspect that is of particular importance is the potential of APG to prevent cerebral ischemia in postmenopausal women, who are more likely to suffer from cerebral ischemia and have a much higher mortality rate than men of the same age. This review has provided evidence on the therapeutic and preventive effects of APG in cerebral ischemia, suggesting the potential values of APG as a candidate medication in future.